Mathematical Modeling of Neuron Using Hodgkin-Huxley Model (Pakistan Journal of Engineering, Technology and Science, 2024)
The growing rate of mental illnesses has brought the idea to cure anxiety disorders through altering heart rate variability using sympathetic and parasympathetic stimulations. The parasympathetic activity in the sinoatrial node being responsible for arrythmia has been considered in the already existing cardiovascular model. This study presents a mathematical model of a single neuron and simulated its activity for a single burst to be amalgamated in a closed-loop system of the heart and uses heart rate variability as a control variable to treat anxiety disorders and decrease the rate of increasing mental disorders in the world population. The proposed study shows the results that rises from 7mV and goes up to 107mV and then again falls back to 7mV depicting a single burst. These results is being validated by comparing the model of neuron presented in classical Hodgkin-Huxley model using MATLAB.
Keywords: Anxiety; Heart rate variability; Sinoatrial node; Mathematical model; Neuron; Mental disorders